MIOCENE PALEOGEOGRAPHIC RECONSTRUCTION IN THE SANGATTA AREA, EAST KALIMANTAN BASED ON CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY AND BENTHONIC FORAMINIFERAL ANALYSIS - Jambak, Moehammad Ali; Deny, Deny; Rendy, Rendy; Syavitri, Dewi (Marine Geological Institute of Indonesia, 2024)
The Kutai Basin is a significant hydrocarbon potential basin with up to 15 km thickness of Tertiary sediments. It is dominated by a complex deltaic system to a marine shelf environment. Thus, it is crucial to understand the facies distribution in the area. This study was carried out to assess, correlate, and reconstruct the paleoceanographic evolution of the basin using lithological and microfossil data obtained from five exploration wells. The lithostratigraphic analysis was used to identify lithological units of each well, while the calcareous nannofossils biostratigraphy was applied to estimate the age and benthic foraminifera was analysed for paleoenvironmental interpretation. The findings reveal that the study region consisted of claystone, siltstone, shale, coal, and sandstone of the Gelingseh and Kelandasan Formation. The age of these lithological units is assigned from the Middle to Late Miocene epoch (NN6-NN11), based on the presence of some nannofossil index fossils such as Catinaster coalitus, Discoaster hamatus, Discoaster quinqueramus, Discoaster calcaris, and Coronocyclus nitescens. Benthic foraminifera assemblages are primarily composed of arenaceous species such as Trochamina spp. and Haplophragmoides spp., indicating a transitional environment, though some species such as Elphidium spp. and several planktonic foraminifera species appeared, which reflect marine influence on the research area. Based on the biofacies analysis; mudflats, tidal flats, delta front, prodelta-marine shelf, and fluvial plain were formed during the Middle to Late Miocene in the studied area.